The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/jcom.12315
|View full text |Cite
|
Sign up to set email alerts
|

Are News Audiences Increasingly Fragmented? A Cross-National Comparative Analysis of Cross-Platform News Audience Fragmentation and Duplication

Abstract: The move to high‐choice media environments has sparked fears over audience fragmentation. We analyze news audiences across media platforms (print, television, and online) in 6 countries, going beyond platform‐specific, single‐country studies. We find surprisingly high levels of news audience duplication, but also that cross‐platform audiences vary from country to country, with fragmentation higher in Denmark and the United Kingdom than in Spain and the United States. We find no support for the idea that online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
145
2
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(178 citation statements)
references
References 39 publications
5
145
2
9
Order By: Relevance
“…Several of our results mirror previous research on populist attitudes and offline news consumption (Schulz 2019b). This speaks for a profound audience duplication and deeply ingrained habits so that people stick to well-known sources (Fletcher and Nielsen 2017), despite their mistrust of the mainstream media. However, the finding that already disaffected citizens turn their back toward the legacy press is a troubling sign for democratic public spheres.…”
Section: Discussionsupporting
confidence: 86%
“…Several of our results mirror previous research on populist attitudes and offline news consumption (Schulz 2019b). This speaks for a profound audience duplication and deeply ingrained habits so that people stick to well-known sources (Fletcher and Nielsen 2017), despite their mistrust of the mainstream media. However, the finding that already disaffected citizens turn their back toward the legacy press is a troubling sign for democratic public spheres.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, spatial and temporal structural changes in media ecosystems-such as digital newsroom integration into public service media (Sehl et al 2018), or changes in opportunity structures of information environment )-are increasingly subject to cross-national comparative analysis. Some recent work on this area has also examined the extent of audience fragmentation across different news media platforms (Fletcher and Nielsen 2017), or day-to-day media diets such as television programming (Lizardo and Skiles 2009) through the lens of comparative, cross-national research. For instance, Fletcher and Nielsen (2017) have found that, while online news audiences are not more fragmented than offline news audiences, there seems to be a higher degree of audience fragmentation in countries with media organizations that offer more diverse content with a high proportion of hard news (e.g.…”
Section: Comparative Research On Media Usementioning
confidence: 99%
“…In this stream of research, assumptions are that increased audience fragmentation-indicated by the fact that news outlets share fewer audiences, especially among those with different ideological slants-leads to higher political polarization. The high-choice media environment, the algorithm-driven news personalization technologies, and the evidence of exacerbated political polarization in US and UK have made these studies prominent in recent publications (see Anspach, 2017;Bakshy, Messing, & Adamic, 2015;Boxell, Gentzkow, & Shapiro, 2017;Del Vicario, Zollo, Caldarelli, Scala, & Quattrociocchi, 2017;Flaxman, Goel, & Rao, 2016;Fletcher & Nielsen, 2017;Prior, 2007;Sunstein, 2017). For example, utilizing Nielsen's panel data, Webster and Ksiazek (2012) presented a long-tail distribution of US news outlets' audience reach and their audience-centric network.…”
Section: Audience-centric Networkmentioning
confidence: 99%